Ion of a Business Plan for Creative Entrepreneurship Among Generation Z in Banjarmasin: The Acrylic Flower Board Initiative - Dhini Dhini; Noor Diana; Norcahaya Norcahaya; Anna Nur Faidah; Sudirwo Sudirwo (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
This socialization activity aims to enhance students' understanding of business planning, particularly in the acrylic flower board decoration industry. The main problem faced by the community partners, who are aspiring student entrepreneurs, is the lack of practical and theoretical knowledge in designing comprehensive and applicable business plans. The proposed solution is integrated training that includes basic business planning theory, marketing strategy, financial analysis, and hands-on simulation focused on creative products. The methods used in this activity involve a combination of material presentations, group discussions, and direct practice in preparing business plans using the acrylic flower board as a case study. The results of the activity indicate a significant increase in students’ interest, understanding, and skills in the business planning process, as evidenced by higher evaluation scores before and after the training.This socialization activity aims to enhance students' understanding of business planning, particularly in the acrylic flower board decoration industry. The main problem faced by the community partners, who are aspiring student entrepreneurs, is the lack of practical and theoretical knowledge in designing comprehensive and applicable business plans. The proposed solution is integrated training that includes basic business planning theory, marketing strategy, financial analysis, and hands-on simulation focused on creative products. The methods used in this activity involve a combination of material presentations, group discussions, and direct practice in preparing business plans using the acrylic flower board as a case study. The results of the activity indicate a significant increase in students’ interest, understanding, and skills in the business planning process, as evidenced by higher evaluation scores before and after the training.